ARRANJO ESPACIAL DAS INDÚSTRIAS DE GUARAPUAVA - PR: UMA ANÁLISE A PARTIR DOS DISTRITOS INDUSTRIAIS - Bravin, Nilvam Jeronimo Ribeiro (2012)
The analysis of arrangement or spatial organization is a relevant topic to geographical science. It should be remembered that after the 1970s, in Brazil and in Paraná, the industrial sector had undergone significant changes, occurring expressively in Guarapuava, which, following the national trend and state, initiating policies aimed at industrial attracting, in order to form and order those dispersed areas. Thus, this research aims to discuss and analyze the industrial sector in Guarapuava, from its eight industrial districts, in order to better understand them. We seek also to examine national and state policies aimed at this sector, beyond the concepts that involve their different organizational structures. From this contribution, which contextualizes and maintains theoretical/methodological this research, we present the industrial profile of Guarapuava systematically constructed from an analysis on the spot.